PEMBUAT IKAN TINAPO - Hasniah .; Syamsumarlin Syamsumarlin; Lisnayanti Lisnayanti (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
The purpose of this study is to determine and to find out the defensive pressure of the families startegies who make the Tinapo fish in Molawe Village, District of Molawe, North Konawe Regency. The informants in this study are 7 families making Tinapo fish, which consists of 4 families of Tinapo fish's producers who have special ponds and 3 families of fish producers who do not have special grills. Data collection of this study is field work directly at the study site using observation techniques and depth interviews. Data analysis is using descriptive qualitative method. The results of the study show that: (1) the pressures faced by the families of the Tinapo fish producers in Molawe Village, District of Molawe, Konawe Utara Regency include the pressure of the natural environment such as raw materials which are not always available like fresh fish, firewood and receding sea water. The pressures are originating by the socio-cultural environment such as the difficulty of obtaining other jobs and the complexity of making Tinapo fish through a long process; (2) the defensive strategy of the family of Tinapo fish producers can be seen from the division of labor in the family of Tinapo fish producers in Molawe Village, District of Molawe, North Konawe regency. It is men who work externally by providing tools and materials such as preparing fish, firewood, fish piercing and grilling fish, while women are more inclined to domestic work such as cleaning fish, piercing fish and marketing the results of making Tinapo fish to the contractor or to the nearest market. Keywords: tinapo fish, family, strategy, pressure, defensive